THE USE OF CIRC COOPERATIVE MODELS USING GRAPHICS MEDIA IN IMPROVING WRITING SKILLS FOR THE FOURTH GRADE STUDENTS OF SDN 2 CANDIWULAN IN ACADEMIC YEAR 2014/2015 - Irani, Emah Ida (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The use of CIRC cooperative models using graphics media in improving writing skills for the fourth grade students of SDN 2 Candiwulan in academic year 2014/2015. The objectives of this research are ) to describe the steps of the implementation of CIRC cooperative models using graphic media, ) to improve writing skills of the fourth grade student, and to describe problems and solutions. This research is a collaborative classroom action research which is conducted in three cycles, each cycle consist of planning, acting, observing, and reflecting. Subjects were fourth grade students of SDN 2 Candiwulan totaling 21 students. Conclusion of this research is the implementation of CIRC cooperative models using graphic media can improve writing skills for the fourth grade students of SDN 2 Candiwulan in academic year 2014/2015. Keyword: CIRC, graphical media, and skill write